Bioaccmulation of Some Heavy Metals in Aquatic Plant Myriophyllum verticilatum (Baghdad Science Journal, 2007)
The present study was invistigated to show the bioaccumulation of some heavy metals (Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Zn) by use Aquatic plant Myriophyllum verticilatum growing in Euphrates river between Spring 2004 to Winter 2005, and these heavy maters was studied in Dissolved and particulat phase of water and exchangable and residual phase of sediment. Heavy metals accumulated according the system water-sediment-aquatic plant, and recorded bioaccumulation factor 1.010, 0.005, 0.009, 0.011, 0.012, 0.010, 0.010, 0.010, 0.011, respectively.